1961
DOI: 10.1530/jrf.0.0020447
|View full text |Cite
|
Sign up to set email alerts
|

Antifertility Substances and Their Assessment in the Male Rodent

Abstract: 1 ) The antifertility effects of a number of simple alkane sulphonic esters have been examined in the male rat by a combination of serial mating of treated animals and histological examination of the testes. The results are compared and contrasted with those obtained with Busulphan (Myleran), dimethylmyleran and various derivatives of ethyleneimine.(2) A spectrum of results on various stages of spermatogenesis has been obtained, which is difficult to reconcile with a common mode of action due to alkylation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
46
0

Year Published

1962
1962
1994
1994

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(51 citation statements)
references
References 6 publications
5
46
0
Order By: Relevance
“…In fertility studies in the rat (Jackson et al, 1961) maximal sensitivity was found in the second and third weeks; a single dose of 50 mg.fkg. causing sterility at this time.…”
Section: Discussionmentioning
confidence: 99%
“…In fertility studies in the rat (Jackson et al, 1961) maximal sensitivity was found in the second and third weeks; a single dose of 50 mg.fkg. causing sterility at this time.…”
Section: Discussionmentioning
confidence: 99%
“…Both MOPP and MVPP were found to produce a very high incidence of azoospermia, with only a few men recovering spermatogenesis after treatment (Chapman et al, 1979;Whitehead et al, 1982). Procarbazine, a component of both regimens, causes complete aplasia of the germinal epithelium in the rat (Jackson et al, 1961) and the non-human primate (Sieber et al, 1978), and mustine and vinblastine are also implicated in the germinal epithelial damage following MOPP/MVPP (Spitz, 1948;Vilar, 1975). Of these, only vinblastine is included in the ABVD regimen, which is reported as causing no permanent gonadal damage.…”
Section: Discussionmentioning
confidence: 99%
“…A single intraperitoneal injection of Busulphan has been reported to cause reversible sterility in rats after about 9 weeks due to an inhibition of sperma¬ togonial development followed by depletion of the seminiferous epithelium by maturation (Jackson, Fox & Craig, 1961). There is, however, no effect on androgenic function of the testes (Jackson et al, 1961) but the total gonado¬ trophin content of the pituitary is reduced (Kar, Jehan, Kamboj, Chowdhury & Chowdhury, 1967).…”
Section: Introductionmentioning
confidence: 99%